PENGARUH KOMPENSASI FINANSIAL DAN NON FINANSIAL TERHADAP MOTIVASI KERJA KARYAWAN PADA BENGKEL UTAMA MOTOR CAKRANEGARA - I GUSTI AGUNG DIDIT EKA PERMADI (GANEC SWARA, 2020)
Aims (1) to determine significant partial effect of financial compensation and non-financial compensation on work motivation  of employees at Bengkel Utama Motor Cakranegara; (2) to determine significant simultant effect of financial compensation and non-financial compensation on work motivation  of employees at Bengkel Utama Motor Cakranegara; (3) to determine dominant effect among financial compensation and non-financial compensastion on work motivation of employee at Bengkel Utama Motor Cakranegara.In accordance with the purpose of research, the type of research used in the research is asosiatif. The population is all of permanent employees about 35 peoples. Determination of the respondents in this study carried out on all members of the population, it has been called a census. To collecte data in this research used questionnaires. To determine the responses of respondents to variables assessed, used Likert Scale analysis with the 5 scale answered point.The conclution of this research showed that : (1) There is a significant partial effect of financial compensation and non-financial compensation on work motivation of employees at Bengkel Utama Motor Cakranegara; (2) There is a significant simultant effect of financial compensation and non-financial compensation of employees at Bengkel Utama Motor Cakranegara; (3) financial compensation has dominant effect on work motivation of employees at Bengkel Utama Motor Cakranegara.